Blended learning as an alternative learning method to support the digital education era - Arifin, Ahmad Zaenal; Sari, Yessi Fatika; Sudrajat, Sudrajat (Jurnal Teori dan Praksis Pembelajaran IPS, 2024)
Learning has now transformed dynamically through the application of technology. This study seeks to determine whether blended learning is an alternative method to support current technological developments. The aim is to analyze the application of blended learning to support the advancement of education through technology. Blended learning will support effective and efficient learning while still paying attention to students' cognitive and critical thinking. This study uses experimental quantitative methods. The researcher developed 15 custom-made questionnaires to be responded to by 20 teachers. Based on the questionnaires, the validity and reliability of blended learning effectiveness were analyzed with SPSS software. The results showed that the questionnaire was valid and reliable, and the fifteen questionnaires analyzed achieved high scores for implementing blended learning. The implications of this research can become a learning option that applies technology so that it is dynamic and supports the digitalization of education.